2020
DOI: 10.1177/0025802420977018
|View full text |Cite
|
Sign up to set email alerts
|

Testing regression and mean model approaches to facial soft-tissue thickness estimation

Abstract: Average facial soft-tissue thickness (FSTT) databanks are continuously developed and applied within craniofacial identification. This study considered and tested a subject-specific regression model alternative for estimating the FSTT values for oral midline landmarks using skeletal projection measurements. Measurements were taken from cone-beam computed tomography scans of 100 South African individuals (60 male, 40 female; Mage = 35 years). Regression equations incorporating sex categories were generated. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…As few new subadults studies were published, only adult studies that reported means and sample size for ≥ 3 landmarks with clear landmark definitions were evaluated. This resulted in 53 new FSTT studies contributing to the 2023 T-Table update, including 33 FSTT studies published between 2018 and 2022 [ 9 , 13 , 124 154 ], and an additional 20 FSTT studies published pre-2018 [ 104 – 123 ] (Table 1 ). These new data include all six main FSTT measurement methods used, so far, for data collection (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As few new subadults studies were published, only adult studies that reported means and sample size for ≥ 3 landmarks with clear landmark definitions were evaluated. This resulted in 53 new FSTT studies contributing to the 2023 T-Table update, including 33 FSTT studies published between 2018 and 2022 [ 9 , 13 , 124 154 ], and an additional 20 FSTT studies published pre-2018 [ 104 – 123 ] (Table 1 ). These new data include all six main FSTT measurement methods used, so far, for data collection (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…As facial approximations are undertaken in the blind, this maneuver tends to inject a degree of subjectivity into the methods. In contrast to FSTT means, regression approaches attempt to tailor estimations more precisely to individuals, typically via craniometric dimensions [ 8 , 9 , 13 , 14 ]. However, just like means, these estimates still retain errors that can sometimes be large.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, this comparison has been performed in a South African FSTT study looking specifically at the mouth-validation testing identified that a population specific approach offered improved results to the total weighted means, when estimating actual soft tissue depth measurements on a hold-out sample. 49…”
Section: Facial Soft Tissue Thickness Datasetmentioning
confidence: 99%